Areas of application of knowledge - Krachunov, Krasnomir (Yearbook Telecommunications, 2017)
1. The main areas of application of knowledge can be determined by the following opposites: material-ideal, perceptions-ideas. These four conditions can be changed and arranged in the following order: material - perceived - presented - ideal. Based on these four basic concepts, a scheme has been developed that gives the possibility for the visualization of the use of knowledge and some conclusions. 2. In order to accomplish this order, the development of communications concepts is monitored. 3. A new communication scheme for the transfer of knowledge has been developed. This scheme has been developed with respect to the objects used in the production and transfer of knowledge. This is indicated in a next new scheme. Conclusion: Objects from the four areas are used notwithstanding for which field knowledge is intended.